(untitled) (Research, Society and Development, 2021)
The increasing waterproofing of urban spaces brings environmental problems and disasters, such as flooding, resulting from changes in rainwater that seep and pass, requiring greater capacity of micro and macro drainage systems. Permeable concrete (CPER), composed of Portland cement and coarse aggregate, gains space as a way to mitigate the effects of reducing permeable areas. In this context, the present work seeks to investigate the influence of the mixing sequence on the hydraulic and mechanical behavior of the roll-milled CPER, given the presence of gaps in the literature about the impact of these parameters on the material. For this, three sequences of mixtures were studied from the production of CPER plates of dimensions 40cmx40cmx10cm. The results of resistance to flexural alteration, porosity, tortuosity and permeability were analyzed. Statistically, no differences were found between the results, however, reduced the volume growth and pore area, changing as sequences when used in the production of concrete or inclined shaft mixer.